The high church revival in the Church of England : arguments and identities - Morris, J. N. 1960- (Anglican-Episcopal Theology and History, 2016)
In The High Church Revival in the Church of England , new insights are opened up into one of the most significant movements of devotional and liturgical revival in the nineteenth and twentieth centuries. Attending closely to the social history of the movement, as well as to its continental connections and its theological complexity, this research re-evaluates its historiographical legacy in the light of recent research and controversy. Traditional interpretations of High Churchmanship have presented it either as a heroic rediscovery of the real essence of Anglicanism, or as an eccentric distortion of it. This volume asserts instead its theological creativity and its popular roots as a permanent enrichment of the Anglican tradition, whilst also analysing and describing the nature and limits of its growth.